2016
DOI: 10.1021/acs.orglett.6b03087
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Undirected Intermolecular C–H Functionalization of Arenes with 3-Diazofuran-2,4-dione: Synthesis of 3-Aryl Tetronic Acids, Vulpinic Acid, Pinastric Acid, and Methyl Isoxerocomate

Abstract: A variety of 3-aryl tetronic acids have been synthesized by an undirected, intermolecular C-H functionalization of arenes with 3-diazofuran-2,4-dione. This methodology featured as a key step in the synthesis of a series of naturally occurring 3-aryl-5-arylidene tetronic acids (pulvinates) from commercially available tetronic acid. Salient features of the pulvinic acid synthesis include a one-step, stereoselective synthesis of the C5 arylidene group and a single step introduction of the C3 aryl substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Tetronic acids, or 4-hydroxy- 5H -furan-2-ones, are found in a range of natural products and are considered as important scaffolds for the construction of bioactive and pharmaceutical compounds . Although several methods for the synthesis of their derivatives have been reported, multiple steps are generally required, e.g., introduction of a substituent at the 3-position of the 2-furanone, protection and deprotection sequences, halogenation or diazotization, and a transition-metal-catalyzed coupling reaction . Also, for substitution at the 5-position, organolithium reagents are generally employed to obtain the corresponding carbanion.…”
mentioning
confidence: 99%
“…Tetronic acids, or 4-hydroxy- 5H -furan-2-ones, are found in a range of natural products and are considered as important scaffolds for the construction of bioactive and pharmaceutical compounds . Although several methods for the synthesis of their derivatives have been reported, multiple steps are generally required, e.g., introduction of a substituent at the 3-position of the 2-furanone, protection and deprotection sequences, halogenation or diazotization, and a transition-metal-catalyzed coupling reaction . Also, for substitution at the 5-position, organolithium reagents are generally employed to obtain the corresponding carbanion.…”
mentioning
confidence: 99%
“…2-( O -tolyl) acetic acid (0.15 g, 1 mmol) was dissolved in 15 mL of methanol, slowly add 2–3 drops of concentrated sulfuric acid, then refluxing for 8 h and monitored by TLC, after the reaction is completed, the solvent methanol was removed by rotary evaporation, 30 mL of water was added to the residue and stirred, extracted three times with ethyl acetate, washed with water, dried and concentrated to give compound 5a . The obtained compound 5a was placed in a round bottom flask, and 1.2 eq of methyl glycolate, 20 mL of tetrahydrofuran, and 2.2 eq of potassium t-butoxide were added, refluxing and stirring the reaction and monitored by TLC, after the reaction is completed, 50 mL of water was added to the residue and stirred, adjust the pH of the solution to 5–6, then extracted three times with ethyl acetate, washed with water, dried and concentrated to obtain key lactone intermediates II ( 6a ) [10,11,12,13,14].…”
Section: Methodsmentioning
confidence: 99%
“…3-Aryl-4-hydroxy-2(5 H )-furanone belongs to the class of natural butenolides, and the core structure of these compounds is a five-membered lactone ring unit, and which is not only a structural fragment contained in many natural products [7,8] but also the core structure of insecticides [9]. As shown in Figure 1, many natural products such as ascorbic acid (vitamin C) and pulvinic acid possess the β-keto-γ-butyrolactone motif, and a lot of butenolide compounds containing this moiety have anti-tumor, anti-inflammatory, antioxidant and other biological activities [10,11,12,13,14,15,16,17]. Studies have shown that in the process of bacterial cell wall synthesis, these butenolide derivatives can inhibit the activity of Mur enzyme to achieve antibacterial action, so it is an antibacterial lead compound with research and development potential [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Although several synthetic preparations of symmetrically substituted pulvinic acids exist, [7,8] only few syntheses of unsymmetrically substituted congeners are reported, including the two known total syntheses of xerocomic acid. [9] The main strategies employed are based on the synthesis of a tetronic acid derivative followed by functionalization via Suzuki-Miyaura [9] couplings, CÀ H functionalization, [10] Wittig reaction, [11] aldolisation [12] or by Reformatsky-type reactions applied to maleic anhydride. [13] Notably, Ramage in 1984 was also able to mimic the final cyclisation of xerocomic acid from a precursor prepared by a conventional construction of a linear precursor.…”
Section: Introductionmentioning
confidence: 99%